DEFECTS IN THE TRAINING OF MEDICAL PERSONNEL IN SOVIET UZBEKISTAN - Kadirjon Najmiddinov Murodjon's Ogli (Western European Studies, 2024)
Training of medical personnel to maintain the health of the population in the Uzbek SSR is considered one of the most important tasks. In this article, it is explained how the training of medical personnel and improvement of their qualifications was started in Soviet Uzbekistan. The issues of educational institutions training medical personnel and their material support are revealed on the basis of various evidences on the example of the regions of the Fergana Valley
Keywords: oncology; dentist; sanitation; Council of Ministers